Diagenetic evolution characteristics of Paleogene lacustrine carbonate reservoirs in central Bohai sea, China - Zhengxiang Lv; Yuanhua Qing; Fu Zhao; Jiayang Wu; Xiandong Wang (Journal of Natural Gas Geoscience, 2018)
The distribution of high-quality reservoirs in Shahejie Formation of the Shijiutuo Uplift, Central Bohai Sea, is the key factor to determine the oil and gas accumulation. Likewise, diagenesis is the key factor to control the development of lacustrine carbonate reservoirs in Shahejie Formation. So, accurately analyzing the diagenesis is very important for improving reservoir prediction. By means of polarizing microscopy, fluorescence microscopy, scanning electron microscopy, cathodoluminescence and electron probe analysis techniques, reservoir characteristics and diagenetic evolution sequence are determined. The diagenetic stage was determined by X-ray diffraction of clay minerals. Gas-liquid inclusion homogenization temperature and oxygen isotope geothermometer are used to analyze the formation period of authigenic carbonate minerals. Bioclastic dolostone is the main type of carbonate rocks, followed by dolarenite. The visceral cavity pores and residual primary intergranular pores are the main reservoir space. The diagenetic evolution sequence is established based on the different occurrences of multistage dolomites and their relationship with other diagenesis phenomena, and the final diagenetic stage is the phase B of mesodiagenesis. The favorable diagenesis for reservoir physical properties is the early formation of the pore-lining dolomite deposited in the eodiagenesis and the grain-coating dolomite deposited in the syndiagenesis, both of which weaken the subsequent mechanical compaction to the reservoir porosity. Keywords: Paleogene, Shahejie Formation, Carbonate rock, Diagenesis, Diagenetic sequence